Tricuspid regurgitant velocity elevation in a three-year old child with sickle cell anemia and recurrent acute chest syndromes reversed not by hydroxyurea but by bone marrow transplantation - Colombatti, Raffaella (PAGEPress Publications, 2011)
Elevated Tricuspid Regurgitant Velocity (TRV) has been related to higher mortality in adults and to hemolysis, lower oxygen saturation during 6-minute walk test and acute chest syndrome (ACS) in children with sickle cell disease (SCD). Hydroxyurea (HU) has reduced TRV value in children and adults. We describe a three year old HbSS child with recurrent ACS, hypoperfusion of the left lung, mild hemolysis and persistent TRV elevation. TRV did not normalize after HU, despite improvement in clinical conditions and in baseline laboratory parameters related to hemolysis and blood viscosity, but normalized after bone marrow transplantation (BMT). Our experience suggests that in young patients, TRV reduction can be a positive concomitant effect of BMT.